SOME TRAVELERS FOR THE VLACHS IN MACEDONIA (Annual of the Faculty of Philosophy in Skopje, 2010)
According to the above mentioned, it can be concluded that the foreign writers of travel books were interested in Vlach who were living in Macedonia and in the Balkan. They wrote important travelogues out of which can be learnt more about the custom, the language and the culture of this population. Particularly, the travelogues point out the courage, pride of this population who not preferring to be brought under the Turks they left their own hearth and home and they started inhabiting the mountains, where they engaged in farming. The Vlach were interested not only in farming but in craftsmanship, trading, renting, and taking different goods over to the Central Europe as well as to the Balkan. It is undeniably that the from the Vlach population descended many notable people who were famous in Macedonia and out of it. Big problem for the Vlach was the Greek propaganda with an intention to assimilate them. However, thanks to the women and their deep attachment to the family they kept their own characteristic.
Keywords: MACEDONIA; VLACH; WRITERS OF TRAVEL BOOKS; BITOLA; THESSALONICA; ROMANIA; ROMANIANS; TRAVELLING